Management control of the red coffee BORER, Zeuzera spp. (LEPIDOPTERA: COSSIDAE) ON Eucalyptus pellita F. MUELL. USING ENTOMOPHATOGENIC FUNGI - Mohamad Suheri,; Ruly Anwar,; Noor Farikhah Haneda,; Hwa Jung, Yoon; Shinichi Sukeno, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The Red Coffee Borer, Zeuzera spp. (Lepidoptera: Cossidae), is one of the major insect pests of Eucalyptus pellita plantations. The larvae may cause holes in stems, thereby reducing log productivity and have difficulty to control the larval stage. The use of biological agents has been carried out, however the application of nematode group as agent is still limited. Integrated Pest Management (IPM) strategy, including biological agents by fungus group, may have potential to control Zeuzera spp. by providing the optimal results. This study aims to analyze the potential use of entomopathogenic fungi (Beaveria bassiana, Metarhizium anisopliae, and Metarhizium majus) in infecting the larvae of Zeuzera spp. in the laboratory and field scale. In the laboratory scale, a non-factorial completely randomized design implemented with 13 treatments and three replications (the total larva of Zeuzera was 78 samples). In the field scale, a randomized block design with one factor (species of entomopathogen) and four planting areas. The application of B. bassiana, M. majus, and M. anisopliae with different conidial densities (108 conidial ml-1, 106 conidial ml-1, 104 conidial ml-1, 102 conidial ml-1, and control) had a significant effect on the mortality of Zeuzera spp. larvae. Entomopathogenic B bassiana at 108 ml-1 causes the highest infection rate of Zeuzera spp. Compare two other fungi. However, there was no significant effect of the application of three species of entomopathogenic fungi on Zeuzera spp. Larvae in young E. pellita in the field. Results from the analysis concluded that entomophatogens have given positive results and potential to control Zeuzera spp. larvae.